Evaluation of roasted soybeans for dairy calves - P.V. Reddy; J.L Morrill; L.S. Bates (Kansas Agricultural Experiment Station Research Reports, 1992)
Diets containing soybeans roasted at different temperatures were fed to calves to investigate effects on growth and feed consumption. A growth trial was conducted using 84 Holstein calves from birth to 8 wk of age. The diets were formulated to contain 18% CP using soybeans roasted at 270 degrees F, 295 degrees F, or 325 degrees F. The overall feed consumption was greater for calves fed the diet containing beans roasted at either 270 or 295 degrees F than those fed the diet containing 325 degrees F beans. A similar trend was observed in weekly feed consumption. Gains were higher for calves fed the diet containing 295 degrees F beans, and these calves were more efficient in converting feed and energy to gain than the others. Rumen undegradable intake protein increased with increasing roasting temperature, but unavailable protein was high for 325 degrees F beans. Superior calf performance resulted when corrected undegradable intake protein (undegradable intake protein "minus" indigestible intake protein) was 56% and trace lipase activity remained.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; Calves; Starter diets; Soybeans; Roasting temperatures